2015
DOI: 10.1038/nature16063
|View full text |Cite
|
Sign up to set email alerts
|

FGF signalling regulates bone growth through autophagy

Abstract: Skeletal growth relies on both biosynthetic and catabolic processes. While the role of the former is clearly established, how the latter contributes to growth-promoting pathways is less understood. Macroautophagy, hereafter referred to as autophagy, is a catabolic process that plays a fundamental part in tissue homeostasis. We investigated the role of autophagy during bone growth, which is mediated by chondrocyte rate of proliferation, hypertrophic differentiation and extracellular matrix (ECM) deposition in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
167
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 30 publications
12
167
1
Order By: Relevance
“…When administered to mice, Tat-Beclin 1 is able to activate autophagy in growth plate chondrocytes (20). We observed that Tat-Beclin 1 administration to WT mice did not affect bone length, growth plate morphology, or chondrocyte function (Supplemental Figure 6, C-E), consistent with previous results (20).…”
Section: Gfp-lc3supporting
confidence: 81%
See 2 more Smart Citations
“…When administered to mice, Tat-Beclin 1 is able to activate autophagy in growth plate chondrocytes (20). We observed that Tat-Beclin 1 administration to WT mice did not affect bone length, growth plate morphology, or chondrocyte function (Supplemental Figure 6, C-E), consistent with previous results (20).…”
Section: Gfp-lc3supporting
confidence: 81%
“…Interestingly, the analysis of craniofacial and dental abnormalities in a LSD mouse model, namely mucolipidosis II (MLII), showed a loss of collagen fibril organization (41), which strikingly resembles the one observed in the cartilage of mice lacking ATG7 in chondrocytes (20).…”
Section: Gfp-lc3mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we took advantage of Tat-beclin1 (Tat-Bec), a specific autophagy-inducing peptide (40), which has been used to enhance autophagy both in vitro and in vivo (41,42). We found that treatment with Tat-Bec with optimized protocol caused an increase in autophagy activity, promoted axonal growth of CNS neurons cultured on a nonpermissive substrate, and prevented axonal degeneration following injury.…”
mentioning
confidence: 99%
“…In the absence of autophagy, collagen molecules abnormally accumulated within the endoplasmic reticulum (ER) of chondrocytes and the levels of Col2 in the cartilaginous ECM was lower in Atg7 chKO compared to control mice. 2 Collagens are synthesized as precursors (procollagens, PCs) in the ER, and undergo several post-translational modifications, which permit the folding and assembly of native triple helix PC chains that are then secreted into the ECM. PCs are large and complex molecules that can be prone to misfolding during assembly and secretion processes.…”
mentioning
confidence: 99%